Dampak Penggunaan Teknologi Informasi Dan Perhatian Orang Tua Terhadap Motivasi Belajar Siswa Kelas V SDN 4 Sragen Tahun Pelajaran 2016/2017 - Hidayah, Nurul, Dra. Ratnasari Diah Utami, M.Si, M.Pd (2017)
This study aims to determine the impact of: (1) use of information technology to motivate students of class V SDN 4 Sragen, (2) the attention of parents to motivate students of class V SDN 4 Sragen, and (3) use of information technology and attention parents to motivate students of class V SDN 4 Sragen. This research method using multivariate correlational survey to process a variety of data to find out the results of his research. This study population as a whole class V 152 students with a sample of 40 students drawn randomly. The technique of collecting data using questionnaires. Data analysis techniques using multiple regression test, t test, F test, determination, the relative contribution and effective contribution, but preceded test instruments and test requirements analysis. Based on the results of the analysis can be concluded: (1) use of information technology has no impact on student motivation based on test results -ttabel t <t <t table is -2.024 <1.949 <2.024. (2) concern the parents had no impact on student motivation based on test results -ttabel t <t <t table is -2.024 <1.679 <2.024. (3) use of information technology and attention of parents affects students' motivation based on test results F F count> Ftable is 4.212> 4.098 or significance <0.05 is 0.022 <0.05. Variable X1 positive impact on variable Y, and X2 positive impact on variable Y with the results of multiple regression test Y = 67.583 + 0.427 X1 + 0,367 X2.